Penentuan Kadar Fenolik dan Flavonoid Total Ekstrak Daun Renggak (Amomum dealbatum Roxb.) dari Berbagai Pelarut Secara Spektrofotometri Uv-Vis - Wismayani, Leni; Roni, Abdul; Minarsih, Tri (Indonesian Journal of Pharmacy and Natural Product, 2022)
Renggak plant (Amomum dealbatum Roxb.) is one of the plants known to contain secondary metabolites such as phenolic and flavonoids compounds that have antioxidant activity. The content of secondary metabolites of renggak leaf extract is strongly influenced by the effectiveness of the solvent in attracting metabolites during the extraction process. The purpose of this study was to determine the effect of different solvents on the total phenolic and flavonoid content of the renggak leaf extract (Amomum dealbatum Roxb.) and to determine the solvent that produced the highest total phenolic and flavonoid content using the Uv-Vis Spectrophotometry method. The results showed that the highest total phenolic and flavonoid content of renggak leaf extract was in methanol extract with a total phenolic content value of 13.2152 mgGAE/g and total flavonoid content of 19.0944 mgQE/g. Based on the results of the statistical analysis of the Tukey Post Hoc test, it was found that there was a significant difference (p<0.05) between the total phenolic and flavonoid levels of the methanol, ethyl acetate and n-hexane extracts where the use of the type of solvent had a significant effect (p<0.05) on the amount of total phenolic and flavonoid content of the renggak leaf extract (Amomum dealbatum Roxb.) produced.ABSTRAKTanaman renggak (Amomum dealbatum Roxb.) merupakan salah satu tanaman yang diketahui mengandung metabolit sekunder seperti senyawa fenolik dan flavonoid sehingga memiliki aktivitas sebagai antioksidan. Kandungan metabolit sekunder ekstrak daun renggak sangat dipengaruhi oleh efektifitas pelarut dalam menarik senyawa metabolit saat proses ekstraksi. Tujuan penelitian ini untuk mengetahui pengaruh perbedaan pelarut terhadap kadar fenolik dan flavonoid total ekstrak daun renggak (Amomum dealbatum Roxb.) serta mengetahui pelarut yang menghasilkan kadar fenolik dan flavonoid total terbesar menggunakan metode Spektrofotometri Uv-Vis. Hasil penelitian didapatkan bahwa rata-rata kadar fenolik dan flavonoid total ekstrak daun renggak tertinggi berada pada ekstrak metanol dengan nilai kadar fenolik total 13,2152 mgGAE/g dan kadar flavonoid total 19,0944 mgQE/g. Berdasarkan hasil analisis statistik Uji Tukey Post Hoc didapatkan bahwa terdapat perbedaan signifikan (p<0,05) antara kadar fenolik dan flavonoid total ekstrak metanol, etil asetat dan n-heksana dimana penggunaan jenis pelarut berpengaruh bermakna (p<0,05) terhadap besarnya kadar fenolik dan flavonoid total ekstrak daun renggak (Amomum dealbatum Roxb.) yang dihasilkan.